SISTEM ENTERPRISE RESOURCES PLANNING SAP DAN KINERJA KEUANGAN EMITEN INDUSTRI FARMASI - Junaedi, Junaedi; Kemalasari, Novawiguna (Universitas Mercu Buana, 2019)
This study aims to analyze the financial performance pre and post enterprise resource planning SAP systems implemented. The chosen variables in this study are ROA, ROE, ROS, ATO, NPM, BEP, sales ratio, and net profit ratio compared during 5 years before and after enterprise resource planning SAP systems implemented. The samples in this study was taken using purposive sampling method. After setting multiple criteria, 4 companies selected as samples. The data analyzed by descriptive analysis method and paired sample t test. This test using IBM SPSS Statistic 21 Program. The result of study shows that there is no differences in ROA, ROE, ROS, ATO, NPM, BEP, sales ratio, and net profit ratio during 5 years before and after enterprise resource planning SAP systems implemented.